Screening of Perinatal Depression Using the Edinburgh Postpartum Depression Scale - Oliveira, Tenilson Amaral; Luzetti, Guilherme Guarany Cardoso Magalhães; Rosalém, Márcia Maria Auxiliadora; Mariani Neto, Corintio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To detect depression during pregnancy and in the immediate postpartum period using the Edinburgh postpartum depression scale (EPDS).Methods Cross sectional study of 315 women, aged between 14 and 44 years, who received perinatal care at the Leonor Mendes de Barros Hospital, in São Paulo, between July 1st, 2019 and October 30th, 2020. The cutoff point suggesting depression was ≥ 12.Results The screening indicated 62 (19.7%) patients experiencing depression. Low family income, multiparity, fewer prenatal appointments, antecedents of emotional disorders, dissatisfaction with the pregnancy, poor relationship with the partner, and psychological aggression were all risk factors associated with depression in pregnancy or in the immediate postpartum period. Antecedents of depression and psychology aggression during pregnancy were significant variables for predicting perinatal depression in the multivariate analysis.Conclusion There is a significant association between the occurrence of perinatal depression and the aforementioned psychosocial factors. Screening patients with the EPDS during perinatal and postpartum care could facilitate establishing a line of care to improve the wellbeing of mother and infant.
Keywords: depression; pregnancy; risk factors; prenatal care; postpartum period